Acrylic pressure-sensitive adhesive matrix-type arnica transdermal patch, preparation method and application
Patent Information
- Application Number
- CN202611078484.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-13
AI Technical Summary
两篇文献均未涉及以医用丙烯酸压敏胶有机相为基质、配合三联增塑促渗体系实现缓释的方案
[0023]本发明的有益效果是:本贴片以低水低多元醇的丙烯酸压敏胶有机相体系替代传统水凝胶基质,从根本上消除了水分迁移、析液和翘边的物理不稳定性来源。经–20℃/40℃各24h循环3次后,贴片翘边率为0%,而水凝胶对比贴片翘边率达65%;在40℃/75%相对湿度加速条件下储存6个月后,总倍半萜内酯(山金车提取物来源)保留率为94.2%,而水凝胶对比贴片仅为72.8%,说明有机相基质对脂溶性活性成分的化学稳定性保护效果明显优于高含水体系。
Smart Images

Figure CN122894340A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of transdermal drug delivery formulation technology, and in particular to an acrylic pressure-sensitive adhesive matrix type arnica transdermal patch, its preparation method and uses. Background Technology
[0002] Arnica montana extract, due to its sesquiterpene lactones (STLs) containing sesquiterpenes, possesses anti-inflammatory and circulation-promoting biological activities and has been widely used in topical formulations to improve skin appearance issues such as sports injuries, post-injection bruising, and local fatigue. Transdermal patches, as a dosage form that enables continuous local drug delivery, are one of the important forms of arnnica topical preparations.
[0003] In existing technologies, transdermal patches containing plant-based active ingredients commonly employ hydrogel systems constructed using partially neutralized polyacrylic acid as a matrix. These systems react polyacrylic acid with an alkaline neutralizing agent (such as sodium hydroxide, triethanolamine, etc.) within a certain degree of neutralization to form a gel network with a specific cross-linking density. Water (typically 30–70% of the formulation) and polyols (typically 20–60%) are used as solvents and moisturizing agents to maintain the gel's softness and adhesion.
[0004] However, hydrogel systems have high water content and strong hygroscopicity. Under alternating low and high temperature storage or use environments, moisture in the gel network is prone to migration or evaporation, leading to patch separation, shrinkage, and even edge lifting, which is particularly noticeable in areas requiring conformal deformation, such as joint flexures and around scars. Meanwhile, the sesquiterpene lactones in the active ingredients of arnica are highly lipid-soluble, with limited solubility and poor chemical stability in high-water-content gel matrices, making them prone to degradation during storage. Furthermore, the high-water-content environment limits the controllability of the release rate, often resulting in a concentrated burst release at the initial application stage, making it difficult to maintain the concentration subsequently, which is detrimental to continuous and stable local delivery.
[0005] The aforementioned defects are all reflected in existing literature. KR102845447B1 discloses a hydrogel catarrhalis patch containing arnica extract (the drug layer contains 30-60% water, with partially neutralized polyacrylic acid as the matrix). This literature itself points out that existing hydrogel patches have problems such as skin irritation, insufficient adhesion, and limited drug penetration. CN117460500A discloses an acrylate copolymer patch containing arnica extract and cannabinoids, which faces regulatory obstacles in multiple markets due to the involvement of cannabinoid components. Neither of the two documents mentions a scheme to achieve sustained release using a medical-grade acrylic pressure-sensitive adhesive organic phase as the matrix, combined with a triple plasticizer and penetration-enhancing system.
[0006] Existing acrylic drug patches often lack a TEC+IPM+DEGEE triple penetration-enhancing system, instead relying on a single penetration enhancer. This results in low drug penetration through the skin and less than 60% release within 24 hours. Furthermore, the lack of a complementary antioxidant system leads to severe degradation of lipid-soluble plant extracts during long-term storage. This invention addresses these shortcomings through a dual approach of synergistic penetration enhancement and antioxidant protection. To address these issues, this invention proposes a low-water-content pressure-sensitive adhesive matrix-based arnica patch, completely resolving the physical instability of hydrogel systems at the matrix level and achieving stable protection and continuous, steady release of lipid-soluble active ingredients. Summary of the Invention
[0007] In view of the above background, the purpose of this invention is to provide a low-water-content acrylic pressure-sensitive adhesive matrix arnica transdermal patch, which completely solves the physical instability of the hydrogel system at the matrix level, and at the same time achieves stable protection of the fat-soluble active ingredients and continuous and stable delivery for 12–24 hours through a triple plasticizing and permeation-promoting system; on this basis, the invention further provides corresponding preparation methods and external applications.
[0008] The specific technical solution of the patch of the present invention is as follows: An acrylic pressure-sensitive adhesive-based arnica transdermal patch, comprising a backing layer, a drug layer, and a release film, characterized in that the drug layer is a non-hydrogel matrix, comprising, by weight percentage: medical acrylic pressure-sensitive adhesive, 85%–94%; arnica supercritical carbon dioxide extract, 0.5%–1.5%, with the total sesquiterpene lactone content derived from the arnica supercritical carbon dioxide extract in the patch being 30–150 µg; triethyl citrate, 2%–5%; isopropyl palmitate, 1%–4%; diethylene glycol monoethyl ether, 1%–5%; antioxidant; wherein the water content of the patch is less than 5%; and the total polyol content is less than 20%.
[0009] Preferably, the medical acrylic pressure-sensitive adhesive is an acrylic-acrylate copolymer pressure-sensitive adhesive with a weight-average molecular weight of 600,000–900,000 Da and a glass transition temperature of –50°C to –30°C.
[0010] Preferably, the content of the triethyl citrate is 3%–4%.
[0011] Preferably, the content of isopropyl palmitate is 2%–3%.
[0012] Preferably, the content of the diethylene glycol monoethyl ether is 2%–3%.
[0013] Preferably, the antioxidant is a composite system of tocopherol and 2,6-di-tert-butyl-4-methylphenol, wherein the content of tocopherol is 0.1%–0.3% and the content of 2,6-di-tert-butyl-4-methylphenol is 0.05%–0.2%.
[0014] Preferably, the mass ratio of tocopherol to 2,6-di-tert-butyl-4-methylphenol is 1:0.2–0.5.
[0015] Preferably, the total sesquiterpene lactone content in the unit patch derived from the supercritical carbon dioxide extract of arnica is 50–120 µg.
[0016] Preferably, the backing layer is a polyurethane film with a thickness of 20–30 µm; the drug layer is the non-hydrogel acrylic pressure-sensitive adhesive drug layer with a dry coating weight of 40–70 g / m²; and the release film is a silicone-modified polyethylene terephthalate film.
[0017] Preferably, the thickness of the polyurethane film is 23–27 µm.
[0018] The corresponding preparation method was specifically optimized for the uniform dispersion of fat-soluble extracts in the organic phase of pressure-sensitive adhesives and the control of residual solvents. The specific scheme is as follows: A method for preparing the above-mentioned acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch includes the following steps: Step (1): The arnica supercritical carbon dioxide extract is mixed with triethyl citrate, isopropyl palmitate and diethylene glycol monoethyl ether, and stirred to disperse to obtain the active ingredient-penetration enhancer premix. Step (2): Add the active ingredient-penetration enhancer premix obtained in step (1) to the medical acrylic pressure-sensitive adhesive solution, add antioxidant, mix evenly and filter to obtain the coating solution; Step (3): The coating solution is coated onto the silicone polyethylene terephthalate release film and dried in an oven until the total amount of residual solvent is not higher than 500 ppm to obtain the drug layer; Step (4): The drug layer is laminated with a polyurethane backing, cured, and then die-cut. The product is sealed in aluminum foil under nitrogen protection to obtain the finished transdermal patch.
[0019] Preferably, in step (1), the stirring and dispersion temperature is 40–60℃, the stirring time is 30–60 min, the stirring rate is 200–400 rpm, and the premixed liquid is filtered through a filter membrane with a pore size of 0.45 µm.
[0020] Preferably, in step (2), the solid content of the coating liquid is 35–55%, and the viscosity of the coating liquid at 25°C is 2,000–8,000 mPa. s.
[0021] Preferably, in step (3), the drying tunnel adopts a segmented heating method, with the first segment temperature being 60–70℃ and the dwell time being 2–4 min, and the second segment temperature being 75–90℃ and the dwell time being 3–5 min; in step (4), the curing temperature is 40–50℃ and the curing time is 24–72 h, and the aluminum foil bag is heat-sealed under nitrogen protection.
[0022] The above-mentioned patch can be used for the following purposes: The use of an acrylic pressure-sensitive adhesive-based arnica transdermal patch in the preparation of a topical anti-inflammatory and circulation-promoting formulation for improving subcutaneous bruising and local skin fatigue caused by sports injuries, injections, or minor impacts. The patch's drug layer is a non-hydrogel matrix, comprising, by dry weight: 85-94% medical-grade acrylic pressure-sensitive adhesive; 0.5-1.5% arnica supercritical carbon dioxide extract; 2-5% triethyl citrate; 1-4% isopropyl palmitate; 1-5% diethylene glycol monoethyl ether; and an antioxidant. The patch contains less than 5% water and less than 20% total polyols.
[0023] The beneficial effects of this invention are as follows: This patch uses a low-water, low-polyol acrylic pressure-sensitive adhesive organic phase system to replace the traditional hydrogel matrix, fundamentally eliminating the sources of physical instability such as water migration, precipitation, and edge curling. After three cycles of -20℃ / 40℃ for 24 hours each, the edge curling rate of the patch was 0%, while the edge curling rate of the hydrogel patch reached 65%. After 6 months of storage under accelerated conditions of 40℃ / 75% relative humidity, the retention rate of total sesquiterpene lactones (derived from arnica extract) was 94.2%, while that of the hydrogel patch was only 72.8%, indicating that the organic phase matrix has a significantly better effect on protecting the chemical stability of fat-soluble active ingredients than the high-water-content system.
[0024] Triethyl citrate, isopropyl palmitate, and diethylene glycol monoethyl ether act on three different permeability barrier layers—matrix diffusion, stratum corneum lipid channels, and aqueous channels—to synergistically cover multiple pathways for enhanced penetration, resulting in a cumulative release rate of over 65% at 24 hours and a release rate of no more than 15% at 0–2 hours, effectively avoiding explosive release. The measured skin retention of the triple system was 28 µg / cm², an increase of approximately 87% compared to the optimal single penetration enhancer group (isopropyl palmitate alone, 15 µg / cm²) and approximately 47% compared to the dual-action group (19 µg / cm²). The combination of the three produced a synergistic penetration-enhancing effect that surpasses simple additive effects.
[0025] The patch employs a three-layer structure, combining a polyurethane backing (20–30µm) and an acrylic pressure-sensitive adhesive layer (dry coating weight 40–70g / m²). With a 180° peel force of 2–5N / 25mm, it balances reliable adhesion with painless removal, making it suitable for long-term application to dynamic areas such as joints, muscles, and around scars. The active ingredient is arnica CO2 supercritical extract, combined with a tocopherol and 2,6-di-tert-butyl-4-methylphenol complex antioxidant system to effectively inhibit oxidative degradation. The total sesquiterpene lactone content (30–150µg / patch) is used as the batch release indicator, detected by HPLC, with an inter-batch RSD not exceeding 5%, ensuring quantifiable quality control. Attached Figure Description
[0026] Figure 1 This is a schematic cross-sectional view of the three-layer patch structure.
[0027] Figure 2 This is a schematic diagram showing the in vitro cumulative release rate versus time for Example 1 and Comparative Example 1.
[0028] Figure 3 A bar chart comparing the 24-hour cumulative release rate and skin retention of each penetration enhancer combination. Detailed Implementation
[0029] The present invention will be further described in detail below with reference to embodiments.
[0030] Unless otherwise specified, all raw materials used in the following examples are commercially available. Arnica CO2 supercritical extract was purchased from Flavex Naturextrakte GmbH, Germany. This extract was prepared using a CO2 supercritical extraction process at an extraction pressure of 200–350 bar, an extraction temperature of 40–60°C, and a CO2 flow rate of 10–20 kg / h. The extract is a dark brown to brownish-green oily liquid with the characteristic odor of arnica; it is highly lipid-soluble, with an octanol / water partition coefficient (logP) of approximately 2.5–3.5; it is completely soluble in a premixed solution of triethyl citrate, isopropyl palmitate, and diethylene glycol monoethyl ether without the need for additional organic solvents.
[0031] The content of total sesquiterpene lactones (STLs, the specific active components of Arnica extract) was determined by high-performance liquid chromatography (HPLC). Trans-helenalin and dihydrohelenalin were used as quantitative markers. A C18 reversed-phase column (250 mm × 4.6 mm, 5 µm) was used, with acetonitrile / water gradient elution as the mobile phase. The detection wavelength was 225 nm, and the relative standard deviation (RSD) of STL content between batches was no higher than 5%. These sesquiterpene lactones are characteristic active components of Arnica, and their determination using trans-helenalin and / or dihydrohelenalin as quantitative markers was performed by HPLC.
[0032] The medical-grade acrylic pressure-sensitive adhesive (acrylic acid-acrylate copolymer, weight average molecular weight approximately 750,000 Da, glass transition temperature approximately –40°C) was an ethyl acetate solution (solid content approximately 50%), purchased from Evonik Industries AG, Germany (trade name Duro-Tak 387-2516). Triethyl citrate, isopropyl palmitate, diethylene glycol monoethyl ether (Transcutol P), tocopherol (mixed type, D-α-tocopherol content ≥96%), and 2,6-di-tert-butyl-4-methylphenol were all pharmaceutical grade and purchased from their respective suppliers. The silicone-modified polyethylene terephthalate release film (silicification amount approximately 1.0 g / m²) and polyurethane backing film (thickness 25 µm) were medical grade, and all solvents were analytical grade.
[0033] In the compound antioxidant system, tocopherol is the main antioxidant component and 2,6-di-tert-butyl-4-methylphenol is the auxiliary antioxidant component. Within the ratio range, the two can synergistically inhibit the oxidative degradation of arnica sesquiterpene lactones. If the proportion of 2,6-di-tert-butyl-4-methylphenol is higher than 0.5, it is easy to cause mild skin irritation. If it is lower than 0.2, the synergistic antioxidant effect will decrease significantly.
[0034] In the following examples, the dry coating weight was determined by weighing (dimming area method); the water content was determined by the Karl Fischer method; the total polyol content was determined by gas chromatography (GC); the residual solvent was determined by headspace gas chromatography (GC); the total sesquiterpene lactone content (characteristic active ingredients of Arnica extract, with trans-tributol and dihydrotributol as quantitative markers) was determined by high performance liquid chromatography (HPLC) using a C18 reversed-phase column (250 mm × 4.6 mm, 5 µm), with acetonitrile / water gradient elution as the mobile phase and a detection wavelength of 225 nm; the 180° peel strength was determined according to the PSTC-101 method, using a stainless steel plate as the substrate, with a peel speed of 300 mm / min; the in vitro release rate was determined using the Franz diffusion cell method, with a diffusion area of 1.77 cm² and a diffusion medium... The artificial skin membrane (Strat-M membrane) was used. The receptor solution was a mixture of phosphate buffer and ethanol at a volume ratio of 7:3. The temperature was 37℃, and the stirring speed was 300 rpm. Samples were taken at specified time points, and the concentration of total sesquiterpene lactones was quantitatively determined by HPLC to calculate the cumulative release rate. The skin retention was determined after the Franz diffusion cell experiment. The artificial skin membrane was removed, and the residual active ingredients in the membrane were extracted with ethanol / water (7:3, volume ratio) and quantitatively determined by HPLC. The results were expressed as µg / cm². The temperature cycling stability test conditions were -20℃ and 40℃ for 24 hours each as one cycle, for a total of 3 cycles. The edge lifting of the patches was visually inspected, and the edge lifting rate was calculated as (number of edge-lifted patches / total number of patches × 100%). The accelerated stability test conditions were 40℃ / 75% relative humidity, stored for 6 months, and the retention rate of total sesquiterpene lactones was determined by HPLC.
[0035] Reference Figure 1 The patch has a three-layer structure, consisting of a backing layer, a drug layer, and a release film. From top to bottom, the backing layer is a polyurethane film (20–30µm), also known as a polyurethane backing film or polyurethane backing layer. The drug layer contains a pressure-sensitive adhesive drug layer with a triple plasticizing and penetration-enhancing system (dry coating weight 40–70g / m², where black dots in the figure represent dispersed particles of arnica supercritical carbon dioxide extract (containing total sesquiterpene lactones)) and a siliconized PET release film.
[0036] The 180° peel force of the patch, measured using a stainless steel plate as the substrate and a peel speed of 300 mm / min, is 2–5 N / 25 mm.
[0037] Using the Franz diffusion cell method, with an artificial skin membrane as the diffusion medium, and a phosphate buffer and ethanol mixture at a volume ratio of 7:3 as the acceptor solution, and measured at 37°C, the cumulative release rate of the patch was not less than 40% after 12 hours, not less than 65% after 24 hours, and not more than 15% after 0–2 hours. All the above in vitro release indicators were determined according to the Franz diffusion cell method of the "Determination of Release Rate of Transdermal Patches" in the 2025 edition of the Chinese Pharmacopoeia, Part IV. The judgment threshold is the steady-state sustained-release standard customized by this invention for the lipid-soluble active ingredients of Arnica.
[0038] Reference Figure 2 The in vitro cumulative release rate versus time curves of Example 1 (triple PSA patch, solid line) and Comparative Example 1 (hydrogel patch, dashed line) are compared (Franz diffusion cell method, Strat-M membrane, PBS / ethanol 7:3, 37℃). Comparative Example 1 released 38% within 0–2 h, exhibiting a burst release; Example 1 released only 9% during the same period, with a cumulative release rate of 71% after 24 h, and the release curve was nearly linear, demonstrating the effective control of the initial burst release by the triple system.
[0039] Reference Figure 3 The study included single penetration enhancer groups (Comparative Examples 2–4), dual-action groups (TEC+IPM), and triple-action systems (Example 1). Note: The values above the columns represent skin retention (µg / cm²), indicating the total arnica sesquiterpene lactone content retained per unit area of artificial skin. The single-action groups showed a 24-hour release rate of 35%–41% and a retention rate of 10–15 µg / cm²; the dual-action groups showed 58% / 19 µg / cm²; and the triple-action system in Example 1 showed 71% / 28 µg / cm², which were 22.4% and 47.4% higher than the optimal dual-action groups, respectively, indicating a significant synergistic effect from the combination of the three agents.
[0040] A method for preparing an acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch, comprising the following steps: (1) 0.5–1.5% of arnica supercritical carbon dioxide extract, 2–5% of triethyl citrate, 1–4% of isopropyl palmitate, and 1–5% of diethylene glycol monoethyl ether are mixed and dispersed by stirring to obtain an active ingredient-penetration enhancer premix; (2) the premix obtained in step (1) is added to a medical acrylic pressure-sensitive adhesive solution, an antioxidant is added, and the mixture is filtered after thorough mixing to obtain a coating solution. The amount of medical acrylic pressure-sensitive adhesive used is such that its content in the dry base of the drug layer is 85-94%; in step (3), the coating liquid is coated on the silicone polyethylene terephthalate release film and dried in an oven until the total amount of residual solvent is not higher than 500 ppm to obtain the drug layer; in step (4), the drug layer obtained in step (3) is laminated with a polyurethane backing, cured and then die-cut, and filled and sealed in an aluminum foil bag under nitrogen protection to obtain the patch; wherein the water content of the patch is less than 5% and the total amount of polyol is less than 20%.
[0041] The use of an acrylic pressure-sensitive adhesive-based arnica transdermal patch in the preparation of a topical anti-inflammatory and circulation-promoting formulation for improving subcutaneous bruising and local skin fatigue caused by sports injuries, injections, or minor impacts. The patch's drug layer is a non-hydrogel matrix, comprising, by dry weight: 85-94% medical-grade acrylic pressure-sensitive adhesive; 0.5-1.5% arnica supercritical carbon dioxide extract; 2-5% triethyl citrate; 1-4% isopropyl palmitate; 1-5% diethylene glycol monoethyl ether; and an antioxidant. The patch contains less than 5% water and less than 20% total polyols.
[0042] Visual bruising refers to skin pigmentation changes caused by subcutaneous hematoma resulting from sports injuries, injections, or minor impacts; the topical preparation is applied to the skin around joints, muscles, or scars for 12–24 hours each time, once daily, for 3–7 consecutive days.
[0043] Example 1 This embodiment prepares an acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to standard formulation A. The drug layer formulation (by dry weight) is as follows: 89.0% medical-grade acrylic pressure-sensitive adhesive, 1.0% arnica supercritical carbon dioxide extract, 3.5% triethyl citrate, 2.5% isopropyl palmitate, 3.0% diethylene glycol monoethyl ether, 0.2% tocopherol, and 0.1% 2,6-di-tert-butyl-4-methylphenol. Since the total proportion of these components is less than 100%, the remainder is made up by the medical-grade acrylic pressure-sensitive adhesive, making the total dry weight 100%. No additional inert fillers are used; only trace amounts of process impurities (<0.7%) are present, which do not affect the matrix's physical properties, release, or stability.
[0044] The preparation steps are as follows: Step (1), add 1.0 part by weight of arnica supercritical carbon dioxide extract to triethyl citrate (3.5 parts), isopropyl palmitate (2.5 parts) and diethylene glycol monoethyl ether (3.0 parts), and stir and disperse at 300 rpm for 45 min under a 50℃ water bath to fully dissolve and disperse the extract. Filter through a 0.45µm polytetrafluoroethylene filter membrane to obtain the active ingredient-penetration enhancer premix, for later use; Step (2), add the supercritical carbon dioxide extract of arnica (1.0 part by weight, the same below) ... filter through a 0.45µm polytetrafluoroethylene filter membrane to obtain the active ingredient-penetration enhancer premix, for later use; Step (2), add the supercritical carbon dioxide extract of arnica (1.0 part by weight, the same below) to triethyl citrate (3.5 parts), isopropyl palmitate (2.5 parts) and diethylene glycol monoethyl ether (3.0 parts), and filter through a 0.45µm polytetrafluoroethylene filter membrane to obtain the active ingredient-penetration enhancer premix, for later use; Step (1) The obtained premixed solution was added to a medical acrylic pressure-sensitive adhesive ethyl acetate solution (solid content 50%, the amount was taken to make the pressure-sensitive adhesive content in the dry basis 89.0 parts), and tocopherol (0.2 parts) and 2,6-di-tert-butyl-4-methylphenol (0.1 parts) were added in sequence. The mixture was stirred evenly at 200 rpm at room temperature. The solid content of the coating solution was adjusted to 45% with ethyl acetate. The solution was filtered through a 0.45µm filter membrane to obtain the coating solution. The viscosity of the coating solution at 25℃ was measured to be 4,200 mPa. s (Brookfield viscometer); Step (3), the coating liquid is coated onto the siliconized surface of the siliconized polyethylene terephthalate release film using a doctor blade coater, with a wet film thickness of 120µm; after coating, it enters the drying tunnel for drying, with segmented heating: the first segment temperature is 65℃, and the residence time is 3min; the second segment temperature is 82℃, and the residence time is 4min; after drying, the residual solvent is detected by headspace gas chromatography, the residual amount of ethyl acetate is 280ppm, and n-hexane is not detected (below the detection limit of 50ppm), both of which meet the internal control standard of residual solvent not exceeding 500ppm, and the drug layer is obtained; Step (4), the drug layer obtained in step (3) is composited with a polyurethane backing film (thickness 25µm) at room temperature, placed in a 45℃ oven for curing for 48h, and after curing, it is die-cut into 5cm×7cm specifications, and heat-sealed in an aluminum foil bag under nitrogen protection to obtain the patch.
[0045] The obtained patches were tested, and the results are as follows: dry coating weight 55 g / m² (±3 g / m², average of 5 measurements); water content (Karl Fischer method) 1.2%, below the 5% limit; total polyol content (gas chromatography) 0%, below the 20% limit; the drug layer does not contain a hydrogel network formed by neutralizing polyacrylic acid with an alkaline neutralizing agent; total sesquiterpene lactones (characteristic active ingredient of Arnica extract) content per patch (5cm×7cm, area 35cm²) (HPLC method) 85µg / patch, within the control range of 30–150µg / patch; 180° peel force (stainless steel plate, 300mm / min) 3.2N / 25mm, within the range of 2–5N / 25mm; initial tack (rolling ball method) 8 ball; holding power (1kg / 25mm) greater than 24h. In vitro Franz diffusion cell release results: 0–2h cumulative release rate 9%, 12h cumulative release rate 48%, 24h cumulative release rate 71%, meeting the performance requirements of 0–2h release rate not higher than 15%, 12h cumulative release rate not lower than 40%, and 24h cumulative release rate not lower than 65%, with no explosive release phenomenon.
[0046] Example 2 This embodiment prepares an acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch with a high triethyl citrate / low isopropyl palmitate formulation B. The drug layer formulation (by dry weight) is as follows: 88.5% medical-grade acrylic pressure-sensitive adhesive, 1.0% arnica supercritical carbon dioxide extract, 4.5% triethyl citrate, 1.5% isopropyl palmitate, 3.0% diethylene glycol monoethyl ether, 0.2% tocopherol, and 0.1% 2,6-di-tert-butyl-4-methylphenol. Since the total proportion of these components is less than 100%, the remainder is made up by the medical-grade acrylic pressure-sensitive adhesive, making the total dry weight 100%.
[0047] The preparation steps are the same as in Example 1, except that: in step (1), the amount of triethyl citrate is adjusted to 4.5 parts and the amount of isopropyl palmitate is adjusted to 1.5 parts; in step (2), the amount of medical acrylic pressure-sensitive adhesive is adjusted accordingly to make the dry basis content 88.5 parts and the coating liquid solid content is adjusted to 45%; in step (3), the wet film thickness is adjusted to 130µm and the drying tunnel conditions remain unchanged; in step (4), the die-cutting specifications and packaging conditions remain unchanged.
[0048] The obtained patches were tested, and the results are as follows: dry coating weight 60 g / m²; water content 1.1%; total polyols 0%; total sesquiterpene lactones (characteristic active ingredient of Arnica extract) content per patch (HPLC method) 92 µg / patch; 180° peel force 3.5 N / 25 mm. In vitro Franz diffusion cell release results: 0–2 h cumulative release rate 8%, 12 h cumulative release rate 55%, 24 h cumulative release rate 78%. Compared with Example 1, the high triethyl citrate content (4.5%) further lowered the glass transition temperature of the acrylic pressure-sensitive adhesive matrix, increased the matrix free volume, and improved the diffusion rate of total sesquiterpene lactones. The 12 h and 24 h cumulative release rates were both higher than in Example 1. Simultaneously, the low isopropyl palmitate content (1.5%) helps reduce the potential irritation of the skin by the lipid penetration enhancer, making it suitable for users with sensitive skin.
[0049] Example 3 This embodiment prepares an acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch with a low diethylene glycol monoethyl ether / high isopropyl palmitate formulation C. The drug layer formulation (by dry weight) is: 89.5% medical-grade acrylic pressure-sensitive adhesive, 1.0% arnica supercritical carbon dioxide extract, 3.5% triethyl citrate, 3.5% isopropyl palmitate, 1.5% diethylene glycol monoethyl ether, 0.2% tocopherol, and 0.1% 2,6-di-tert-butyl-4-methylphenol. Since the total proportion of these components is less than 100%, the remainder is made up by the medical-grade acrylic pressure-sensitive adhesive, and the total dry weight is 100%.
[0050] The preparation steps are the same as in Example 1, except that: in step (1), the amount of isopropyl palmitate is adjusted to 3.5 parts and the amount of diethylene glycol monoethyl ether is adjusted to 1.5 parts; in step (2), the amount of medical acrylic pressure-sensitive adhesive is adjusted accordingly to make the dry basis content 89.5 parts and the coating liquid solid content is adjusted to 45%; in step (3), the wet film thickness is adjusted to 110µm and the drying tunnel conditions remain unchanged; in step (4), the die-cutting specifications and packaging conditions remain unchanged.
[0051] The obtained patches were tested, and the results are as follows: dry coating weight 50 g / m²; water content 1.8%, less than 5%; total polyols 0%; total sesquiterpene lactones (characteristic active ingredient of Arnica extract) content (HPLC method) 80 µg / patch; 180° peel force 3.8 N / 25 mm. In vitro Franz diffusion cell release results: cumulative release rate 11% at 0–2 h, 42% at 12 h, and 66% at 24 h, meeting the release rate requirements at each time point. The high isopropyl palmitate content (3.5%) enhances the lipid-soluble penetration channels, while the low diethylene glycol monoethyl ether content (1.5%) reduces the patch's hygroscopicity. Under high humidity conditions (80% relative humidity), the peel force retention rate reaches 92%, making it suitable for long-term application to joint flexures, muscles, and other sweaty dynamic areas.
[0052] Comparative Example 1 This comparative example prepared a partially neutralized polyacrylic acid hydrogel arnica patch for performance comparison with the embodiments of the present invention. The hydrogel drug layer formulation is as follows: 20% partially neutralized polyacrylic acid (60% neutralization, neutralized with triethanolamine, polyacrylic acid weight-average molecular weight approximately 1,000,000 Da); 30% glycerin; 50% water (including the amount of water required for the above glycerin and polymer); an appropriate amount of arnica alcohol extract (total sesquiterpene lactones (characteristic active ingredient of arnica extract) content determined by HPLC, ensuring the STL load per patch is the same as in Example 1, approximately 85 µg / patch); free of triethyl citrate, isopropyl palmitate, and diethylene glycol monoethyl ether; free of tocopherol and 2,6-di-tert-butyl-4-methylphenol.
[0053] Preparation method: Dissolve polyacrylic acid in water, add glycerin and arnica alcohol extract, stir evenly, and adjust the neutralization degree to 60% with triethanolamine to form a gel. Coat the gel onto polyethylene terephthalate release film with a dry coating weight of 55g / m², cover with polyurethane backing (25µm), die-cut to 5cm×7cm, and package in aluminum foil bags.
[0054] The patch obtained in Comparative Example 1 was tested, and the results are as follows: water content (Karl Fischer method) 48.5%, total polyol content (gas chromatography) 29.8%, the drug layer contains a hydrogel network formed by neutralizing polyacrylic acid with triethanolamine; 180° peel force 2.8N / 25mm.
[0055] Comparative Example 2 This comparative example prepared an acrylic pressure-sensitive adhesive matrix patch containing only triethyl citrate (a single penetration enhancer). The drug layer formulation (based on dry weight) was: 92.5% medical acrylic pressure-sensitive adhesive, 1.0% arnica supercritical carbon dioxide extract, 3.5% triethyl citrate, 0.2% tocopherol, and 0.1% 2,6-di-tert-butyl-4-methylphenol; excluding isopropyl palmitate and diethylene glycol monoethyl ether; the total proportion of the above components was less than 100%, with the remainder being supplemented by medical acrylic pressure-sensitive adhesive, resulting in a total dry weight of 100%. The preparation steps were the same as in Example 1, except that in step (1), the arnica supercritical carbon dioxide extract was mixed and pre-dispersed with triethyl citrate; the remaining steps remained unchanged. The dry coating weight was 55 g / m², the total sesquiterpene lactone content (characteristic active ingredient of arnica extract) per patch was 85 µg / patch, the water content was 1.3%, and the total polyol content was 0%.
[0056] Comparative Example 3 This comparative example prepared an acrylic pressure-sensitive adhesive matrix patch containing only isopropyl palmitate (a single penetration enhancer). The drug layer formulation (based on dry weight) was: 93.5% medical acrylic pressure-sensitive adhesive, 1.0% arnica supercritical carbon dioxide extract, 2.5% isopropyl palmitate, 0.2% tocopherol, and 0.1% 2,6-di-tert-butyl-4-methylphenol; excluding triethyl citrate and diethylene glycol monoethyl ether; the total proportion of the above components was less than 100%, with the remainder being supplemented by medical acrylic pressure-sensitive adhesive, resulting in a total dry weight of 100%. The preparation steps were the same as in Example 1, except that in step (1), the arnica supercritical carbon dioxide extract was mixed and pre-dispersed with isopropyl palmitate; the remaining steps remained unchanged. The dry coating weight was 55 g / m², the total sesquiterpene lactone content (characteristic active ingredient of arnica extract) per patch was 85 µg / patch, the water content was 1.4%, and the total polyol content was 0%.
[0057] Comparative Example 4 This comparative example prepared an acrylic pressure-sensitive adhesive matrix patch containing only diethylene glycol monoethyl ether (a single penetration enhancer). The drug layer formulation (based on dry weight) was: 93.5% medical acrylic pressure-sensitive adhesive, 1.0% arnica supercritical carbon dioxide extract, 3.0% diethylene glycol monoethyl ether, 0.2% tocopherol, and 0.1% 2,6-di-tert-butyl-4-methylphenol; excluding triethyl citrate and isopropyl palmitate; the total proportion of the above components was less than 100%, with the remainder being supplemented by medical acrylic pressure-sensitive adhesive, resulting in a total dry weight of 100%. The preparation steps were the same as in Example 1, except that in step (1), the arnica supercritical carbon dioxide extract was mixed and pre-dispersed with diethylene glycol monoethyl ether, while the other steps remained unchanged. The dry coating weight was 55 g / m², the total sesquiterpene lactone content (characteristic active ingredient of arnica extract) per patch was 85 µg / patch, the water content was 1.5%, and the total polyol content was 0%.
[0058] Example 4 This embodiment prepares an acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch with lower limit formulation D to verify the feasibility and performance of the product at lower dosages of each core component. The drug layer formulation (by dry basis total weight) is: 85.0% medical-grade acrylic pressure-sensitive adhesive, 0.5% arnica supercritical carbon dioxide extract, 2.0% triethyl citrate, 1.0% isopropyl palmitate, 1.0% diethylene glycol monoethyl ether, 0.1% tocopherol, and 0.05% 2,6-di-tert-butyl-4-methylphenol. Since the total proportion of the above components is less than 100%, the remainder is made up by the medical-grade acrylic pressure-sensitive adhesive, and the total dry basis weight is 100%.
[0059] The preparation steps are the same as in Example 1, except that: in step (1), the amount of arnica CO2 supercritical extract is adjusted to 0.5 parts, the amount of triethyl citrate is adjusted to 2.0 parts, the amount of isopropyl palmitate is adjusted to 1.0 parts, and the amount of diethylene glycol monoethyl ether is adjusted to 1.0 parts; in step (2), the amount of medical acrylic pressure-sensitive adhesive is adjusted accordingly to make the dry basis content 85.0 parts, the amount of tocopherol is adjusted to 0.1 parts, the amount of 2,6-di-tert-butyl-4-methylphenol is adjusted to 0.05 parts, and the solid content of the coating liquid is adjusted to 40%; in step (3), the wet film thickness is adjusted to 100µm, and the drying tunnel conditions remain unchanged; in step (4), the die-cutting specifications and packaging conditions remain unchanged.
[0060] The obtained patches were tested, and the results are as follows: dry coating weight 45 g / m²; water content (Kal Fischer method) 1.0%, below the 5% limit; total polyols (gas chromatography) 0%; total sesquiterpene lactones (characteristic active ingredient of Arnica extract) content per patch (5cm×7cm, area 35cm²) (HPLC method) 30 µg / patch, within the lower limit of the control range of 30–150 µg / patch; 180° peel force (stainless steel plate, 300mm / min) 2.3 N / 25mm, within the range of 2–5 N / 25mm. In vitro Franz diffusion cell release results: cumulative release rate 7% at 0–2h, 41% at 12h, and 67% at 24h, meeting the release performance requirements at each time point. This demonstrates that even when the lower limit dosage of each core component is used, the triple plasticizer and penetration enhancer system can still meet the release performance requirements, and the lower limit values of each component are sufficiently feasible.
[0061] Example 5 This embodiment prepares an acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch with formulation E at the upper limit boundary to verify the feasibility and performance of the product at higher dosages of triethyl citrate and isopropyl palmitate. Since the sum of the upper limits of each component exceeds 100%, this embodiment selects formulations where both triethyl citrate (5.0%) and isopropyl palmitate (4.0%) are at their upper limits for verification. The drug layer formulation (by dry basis total weight) is: 85.5% medical acrylic pressure-sensitive adhesive, 1.5% arnica CO2 supercritical extract, 5.0% triethyl citrate, 4.0% isopropyl palmitate, 3.0% diethylene glycol monoethyl ether, 0.3% tocopherol, and 0.2% 2,6-di-tert-butyl-4-methylphenol. Since the sum of the above component proportions is less than 100%, the remainder is made up by the medical acrylic pressure-sensitive adhesive, and the total dry basis total weight is 100%. In this formulation, both triethyl citrate (5.0%) and isopropyl palmitate (4.0%) are at the upper limit of their defined ranges to verify the performance boundaries of the patch under high plasticizer / high penetration enhancer dosages.
[0062] The preparation steps are the same as in Example 1, except that: in step (1), the amount of arnica CO2 supercritical extract is adjusted to 1.5 parts, the amount of triethyl citrate is adjusted to 5.0 parts, the amount of isopropyl palmitate is adjusted to 4.0 parts, and the amount of diethylene glycol monoethyl ether is adjusted to 3.0 parts; in step (2), the amount of medical acrylic pressure-sensitive adhesive is adjusted accordingly to make the dry basis content 85.5 parts, the amount of tocopherol is adjusted to 0.3 parts, the amount of 2,6-di-tert-butyl-4-methylphenol is adjusted to 0.2 parts, and the solid content of the coating liquid is adjusted to 42%; in step (3), the wet film thickness is adjusted to 145µm, and the drying tunnel conditions remain unchanged; in step (4), the die-cutting specifications and packaging conditions remain unchanged.
[0063] The obtained patches were tested, and the results are as follows: dry coating weight 68 g / m²; water content 1.3%, less than 5%; total polyols 0%, less than the limit requirement of 20%; the drug layer does not contain a hydrogel network formed by neutralizing polyacrylic acid with an alkaline neutralizing agent; total sesquiterpene lactones (characteristic active ingredient of arnica extract) content per patch (HPLC method) 148 µg / patch, within the control range of 30–150 µg / patch; 180° peel force 4.8 N / 25 mm, within the range of 2–5 N / 25 mm. In vitro Franz diffusion cell release results: cumulative release rate 14% at 0–2 h, 62% at 12 h, and 82% at 24 h, meeting the performance requirements of a release rate not exceeding 15% at 0–2 h, not less than 40% at 12 h, and not less than 65% at 24 h. Compared with Example 1, the synergistic effect of high triethyl citrate content (5.0%) and high isopropyl palmitate content (4.0%) increased the cumulative release rate to 82% in 24 hours and 62% in 12 hours. At the same time, the release rate in 0–2 hours was still controlled within 14%, and no explosive release occurred. This proves that when the upper limit of each core component is taken, the triple plasticizer and penetration enhancer system can still maintain steady-state slow-release characteristics and has sufficient feasibility for implementation.
[0064] Example 6 This embodiment is a verification formula for medical acrylic pressure-sensitive adhesive with an upper limit of 94%. The pressure-sensitive adhesive is taken as the maximum value of the range of 94.0%, and all other functional components are taken as the lower limit. This embodiment verifies all performance properties of patch forming, adhesion, sustained release, and storage stability under high adhesive content, and fully covers the entire value range of 85-94%.
[0065] Dry base formulation of the drug layer (total 100%) Medical grade acrylic pressure-sensitive adhesive: 94.0% Arnica supercritical carbon dioxide extract: 0.5% Triethyl citrate: 2.0% Isopropyl palmitate: 1.0% Diethylene glycol monoethyl ether: 1.0% Tocopherol: 0.1% (lower limit of antioxidants) 2,6-Di-tert-butyl-4-methylphenol: 0.05% The total proportion of the above components is less than 100%, and the remainder is made up by medical acrylic pressure-sensitive adhesive. The total dry weight is 100%. There are no additional inert fillers, only trace amounts of process impurities, which do not affect product performance.
[0066] Preparation process (same as in Example 1, only the raw material ratio and wet film thickness are adjusted). 1) Preparation of premix: 0.5 parts of Arnica CO2 supercritical extract + 2.0 parts of TEC + 1.0 parts of IPM + 1.0 parts of DEGEE, stir at 50℃ and 300rpm for 45min, and filter through a 0.45μm filter membrane; 2) Coating solution preparation: Add Evonik Duro-Tak 387-2516 pressure-sensitive adhesive solution to the premixed solution to adjust the dry basis pressure-sensitive adhesive ratio to 94.0%. Add 0.1 parts tocopherol and 0.05 parts BHT, and adjust the solid content to 40% with ethyl acetate. The viscosity at 25℃ is 2600 mPa. s; 3) Coating and drying: wet film thickness 90μm; drying tunnel first stage 65℃ / 3min, second stage 82℃ / 4min; residual solvent after drying 245ppm < 500ppm; 4) Composite curing: 25μm polyurethane backing is laminated, cured at 45℃ for 48h, die-cut to 5cm×7cm, and sealed with nitrogen aluminum foil.
[0067] Complete test data 1) Physical properties: Dry coating weight 42g / m²; Water content 1.0% (<5%); Total polyols 0% (<20%). 2) Active ingredient load: Total sesquiterpene lactones (characteristic active ingredients of arnica extract) per patch: 32 μg / patch, falling within the range of 30–150 μg; 3) Adhesion performance: 180° peel force 2.1N / 25mm (2–5N range); initial adhesion to No. 7 rolling ball; holding power >24h; 4) In vitro sustained release (Franz pool): 0–2h cumulative release rate 6% (≤15%); 12h cumulative release rate 43% (≥40%); 24h cumulative release rate 66% (≥65%), no burst release; 5) Stability test: After 3 cycles of -20℃ / 40℃ thermal cycling, the edge curling rate was 0%; after 6 months of accelerated cycling at 40℃ / 75RH, the sesquiterpene lactone retention rate was 93.7%; 6) Skin irritation: Draize test PII=0.28, indicating no irritation.
[0068] Example of effect 1 This example compares the in vitro release performance, physical stability, and accelerated storage stability of Example 1 and Comparative Example 1 to verify the technical superiority of the non-hydrogel acrylic pressure-sensitive adhesive matrix system of the present invention over the existing hydrogel system.
[0069] In vitro release assays were performed using the Franz diffusion cell method with a diffusion area of 1.77 cm². The diffusion medium was an artificial skin membrane (Strat-M membrane), and the receptor solution was a mixture of phosphate buffer (pH 7.4) and ethanol at a volume ratio of 7:3. The temperature was 37°C, and the stirring rate was 300 rpm. Samples were taken at 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 12 h, 16 h, 20 h, and 24 h. The concentration of total sesquiterpene lactones (characteristic active ingredient of Arnica extract) was determined by HPLC, and the cumulative release rate was calculated. Temperature cycling stability test: The patch was frozen at -20°C for 24 h and then transferred to a 40°C oven for 24 h, constituting one cycle. Three cycles were performed, and the patch edge curling was visually inspected, and the curling rate was recorded. Accelerated stability test: The patch was stored at 40°C / 75% relative humidity for 6 months. Samples were taken, and the total sesquiterpene lactone content was determined by HPLC, and the retention rate relative to the initial content was calculated. The test results are summarized in Table 1.
[0070] Table 1. Comparison of in vitro release, physical stability, and accelerated stability between Example 1 and Comparative Example 1
[0071] Table 1 provides a clear overview of the data. Example 1 showed a 9% release rate over 0–2 hours, while the hydrogel patch in Comparative Example 1 achieved 38% during the same period. The latter, after a concentrated release in the initial application, had limited ability to maintain concentration, hindering stable delivery. In the temperature cycling test, all 20 patches in Example 1 showed no edge curling, while 13 patches in Comparative Example 1 (65%) curled. In the accelerated stability test, the active ingredient retention rate in Example 1 was 94.2%, compared to only 72.8% in Comparative Example 1. All three test results consistently demonstrate that the pressure-sensitive adhesive organic phase matrix is superior to the hydrogel system in both physical stability and chemical stability of the active ingredients. The triple plasticizing and penetration-enhancing system effectively controlled the release rate, and the combination of the two achieved a better overall effect.
[0072] Example of effect 2 This study compares the in vitro release and skin retention of Example 1 (triple penetration enhancer system) with Comparative Examples 2–4 (single penetration enhancer) and the dual penetration enhancer system of triethyl citrate and isopropyl palmitate to verify the synergistic penetration enhancer effect of the triple plasticizer system.
[0073] The formulations of each test group are as follows: Example 1 (triple system): 3.5 wt% triethyl citrate + 2.5 wt% isopropyl palmitate + 3.0 wt% diethylene glycol monoethyl ether; Comparative Example 2 (triethyl citrate alone): 3.5 wt% triethyl citrate; Comparative Example 3 (isopropyl palmitate alone): 2.5 wt% isopropyl palmitate; Comparative Example 4 (diethylene glycol monoethyl ether alone): 3.0 wt% diethylene glycol monoethyl ether; Dual control: 3.5 wt% triethyl citrate + 2.5 wt% isopropyl palmitate. The remaining formulations (medical acrylic pressure-sensitive adhesive, arnica supercritical carbon dioxide extract, antioxidants) and preparation processes of each group are the same as those of Example 1. The total sesquiterpene lactone content per patch of each group is specified as 85 µg / patch.
[0074] The in vitro release test method was the same as in Example 1. Skin retention determination: After the Franz diffusion cell experiment ended (24 h), the artificial skin membrane was removed, and the total residual sesquiterpene lactones in the membrane were extracted with ethanol / water (7:3, volume ratio), and quantified by HPLC. The results are expressed as µg / cm².
[0075] The test results are summarized in Table 2.
[0076] Table 2. Comparison of 24-hour cumulative release rate and skin retention between the triple penetration-enhancing system and the single and dual penetration-enhancing agent control groups.
[0077] As shown in Table 2, the 24-hour release rate and skin retention increased stepwise from the single-component group to the dual-component group and then to the triple-component system: 35%–41% / 10–15 µg / cm² for the single-component group, 58% / 19 µg / cm² for the dual-component group, and 71% / 28 µg / cm² for the triple-component system. Notably, the increase in release rate and skin retention after adding the third component, DEGEE (22.4% and 47.4%, respectively), exceeded the expected contribution of DEGEE alone (35% / 10 µg / cm²), indicating a synergistic effect among the three components. This synergistic effect is related to the different sites of action of the three components: TEC acts on matrix phase diffusion, IPM acts on stratum corneum lipid channels, and DEGEE acts on stratum corneum aqueous phase channels; the three are complementary, covering multiple layers of the permeability barrier.
[0078] Example of effect 3 This example demonstrates the skin irritation of the patch obtained in Example 1 using the Draize test to verify the skin safety of the acrylic pressure-sensitive adhesive matrix arnica transdermal patch of the present invention, providing safety data support for its application.
[0079] The experimental methods were performed in accordance with ISO 10993-10 "Biological evaluation of medical devices—Part 10: Skin sensitization tests" and OECD 404 "Acute skin irritation / corrosiveness tests". Six healthy New Zealand white rabbits (half male and half female, weighing 2.5–3.0 kg) were selected. Twenty-four hours prior to the test, the rabbits were shaved on their backs, exposing approximately 10 cm × 15 cm of skin. Only rabbits whose skin was confirmed to be intact and undamaged by a veterinarian were included in the study. The patch (5 cm × 7 cm) obtained in Example 1 was applied to the intact skin area on the back of each animal and secured with medical tape for 24 hours. After 24 hours of application, the patch was gently removed. The skin at the application site was visually observed at 1 hour, 24 hours, 48 hours, and 72 hours after removal. Erythema / eschar (0–4 points, 0 points: no erythema; 1 point: very slight erythema; 2 points: obvious erythema; 3 points: moderate to severe erythema; 4 points: severe erythema to eschar formation) and edema (0–4 points, 0 points: no edema; 1 point: very slight edema; 2 points: slight edema; 3 points: moderate edema; 4 points: severe edema) were scored independently according to the Draize scoring system. The total stimulation score for each animal at each time point was calculated, and the mean of the scores of 6 animals was used to calculate the Primary Irritation Index (PII). PII < 0.5 is considered "non-irritating", 0.5 ≤ PII < 2.0 is considered "slightly irritating", 2.0 ≤ PII < 5.0 is considered "moderately irritating", and PII ≥ 5.0 is considered "severely irritating".
[0080] The test results are summarized in Table 3.
[0081] Table 3. Results of the Draize Skin Irritation Test for Example 1
[0082] As shown in Table 3, the average erythema score of the patch in Example 1 was only 0.5 points 1 hour after removal, and the skin appearance completely returned to normal after 72 hours, with a PII of 0.3, indicating no irritation. The amount of isopropyl palmitate in the triple system (1–4%) is lower than the irritation threshold (>5%) usually reported in the literature. The synergistic penetration-enhancing mechanism keeps the dosage of each component within a safe range, resulting in good skin tolerance and supporting long-term application to the skin around joints and scars.
[0083] Example of effect 4 This efficacy example uses a standardized subcutaneous bruising animal model to quantitatively evaluate the efficacy of the patch obtained in Example 1 in improving visible bruising, in order to verify the use of the patch of the present invention in reducing visible bruising and to provide efficacy data support for the use claims.
[0084] A standardized subcutaneous hematoma animal model was established using a standardized subcutaneous injection of physiological saline. Twelve healthy New Zealand white rabbits (half male and half female, weighing 2.5–3.0 kg) were randomly divided into three groups (n=4 per group): the patch group (Example 1), the blank PSA patch control group (acrylic pressure-sensitive adhesive patch without arnica extract), and the positive control group (commercially available arnica gel with 10% arnica extract content). 0.2 mL of physiological saline was injected subcutaneously into the back of each animal to establish a standardized subcutaneous hematoma model; the baseline was D0. From D0 onwards, each group received the corresponding preparation once daily. The patch was applied for 12 hours each time, and the gel was applied twice each time, for a total of 7 days (D1–D7). Melanin Index (MI) and Erythema Index (EI) of the bruised areas were measured using a Mexameter MX18 skin colorimeter at times D0, D1, D3, D5, and D7. The percentage decrease (reduction rate %) relative to the baseline at D0 was calculated. Statistical analysis was performed using one-way ANOVA and Tukey's post-hoc test. A p-value < 0.05 was considered statistically significant.
[0085] The experimental results are summarized in Table 4. Table 4 shows the percentage reduction in melanin index (MI) and erythema index (EI) of the bruised areas relative to baseline (D0) for each group.
[0086] Table 4
[0087] Example 1 shows that the patch is significantly more effective than the blank patch in reducing subcutaneous ecchymosis and melanin deposition (p<0.05 / p<0.01), and its efficacy is superior to commercially available single arnica hydrogel formulation. This demonstrates that the low-water non-aqueous matrix + triple penetration-enhancing system can improve the skin penetration and local retention of active ingredients, and provide long-lasting anti-inflammatory and circulation-promoting effects.
Claims
1. An acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch, the patch comprising a backing layer, a drug layer, and a release film, characterized in that, The drug layer is a non-hydrogel matrix, and the drug layer comprises, by weight percentage: Medical-grade acrylic pressure-sensitive adhesive, with a content of 85%–94%; Arnica supercritical carbon dioxide extract, with a content of 0.5%–1.5%, and the total sesquiterpene lactone content derived from the arnnica supercritical carbon dioxide extract in the patch is 30–150 µg; Triethyl citrate, with a content of 2%–5%; Isopropyl palmitate, in a concentration of 1%–4%; Diethylene glycol monoethyl ether, with a content of 1%–3%; Antioxidants; The patch has a water content of less than 5% and a total polyol content of less than 20%.
2. The acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to claim 1, characterized in that, The medical acrylic pressure-sensitive adhesive is an acrylic-acrylate copolymer pressure-sensitive adhesive with a weight-average molecular weight of 600,000–900,000 Da and a glass transition temperature of –50°C to –30°C.
3. The acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to claim 1, characterized in that, The content of the triethyl citrate is 3%–4%.
4. The acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to claim 1, characterized in that, The content of isopropyl palmitate is 2%–3%.
5. The acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to claim 1, characterized in that, The content of the diethylene glycol monoethyl ether is 2%–3%.
6. The acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to claim 1, characterized in that, The antioxidant is a composite system of tocopherol and 2,6-di-tert-butyl-4-methylphenol, wherein the content of tocopherol is 0.1%–0.3% and the content of 2,6-di-tert-butyl-4-methylphenol is 0.05%–0.2%.
7. The acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to claim 6, characterized in that, The mass ratio of tocopherol to 2,6-di-tert-butyl-4-methylphenol is 1:0.2–0.
5.
8. The acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to claim 1, characterized in that, The total sesquiterpene lactone content of the arnica supercritical carbon dioxide extract is 50–120 µg.
9. The acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to claim 1, characterized in that, The backing layer is a polyurethane film with a thickness of 20–30 μm; the dry coating weight of the drug layer is 40–70 g / m²; and the release film is a silicone-modified polyethylene terephthalate film.
10. The acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to claim 9, characterized in that, The thickness of the polyurethane film is 23–27 μm.
11. A method for preparing an acrylic pressure-sensitive adhesive matrix-based arnica transdermal patch according to any one of claims 1-10, characterized in that, include: Step (1): Mix the arnica supercritical carbon dioxide extract with triethyl citrate, isopropyl palmitate and diethylene glycol monoethyl ether, stir and disperse to obtain the active ingredient-penetration enhancer premix; Step (2): Add the active ingredient-penetration enhancer premix obtained in step (1) to the medical acrylic pressure-sensitive adhesive solution, add antioxidant, mix evenly and filter to obtain the coating solution; Step (3): The coating solution is coated onto the silicone polyethylene terephthalate release film and dried in an oven until the total amount of residual solvent is not higher than 500 ppm to obtain the drug layer; Step (4): The drug layer is laminated with a polyurethane backing, cured, and then die-cut. The product is sealed in aluminum foil under nitrogen protection to obtain the finished transdermal patch.
12. The preparation method according to claim 11, characterized in that, In step (1), the stirring and dispersion temperature is 40–60℃, the stirring time is 30–60 min, the stirring rate is 200–400 rpm, and the premixed liquid is filtered through a filter membrane with a pore size of 0.45 µm.
13. The preparation method according to claim 11, characterized in that, In step (2), the solid content of the coating liquid is 35%–55%, and the viscosity of the coating liquid at 25°C is 2,000–8,000 mPa. s.
14. The preparation method according to claim 11, characterized in that, In step (3), the drying tunnel adopts a segmented heating method. The temperature of the first segment is 60–70℃ and the dwell time is 2–4 min. The temperature of the second segment is 75–90℃ and the dwell time is 3–5 min. In step (4), the ripening temperature is 40–50℃ and the ripening time is 24–72 h.
15. The use of an acrylic pressure-sensitive adhesive matrix arnica transdermal patch according to any one of claims 1-10 in the preparation of a topical anti-inflammatory and circulation-promoting preparation.
Citation Information
Patent Citations
Pain relieving patch
CN117460500A
Hydrogel patch composition using arnica extract
KR102845447B1